Biotinidase Deficiency: Report of a Tunisian Case With Neuromyelitis Optica-Like Presentation and Review of the Literature - Abir Zioudi; Hanene Benrhouma; Maha Jamoussi; Thouraya Ben Younes; Zouhour Miladi; Hedia Klaa; Sonia Nagi; Brahim Tabarki; Ilhem Ben Youssef Turki; Ichraf Kraoua (Case Reports in Neurological Medicine)
Biotinidase deficiency is a rare treatable metabolic disorder caused by biallelic mutations in the BTD gene. In the absence of neonatal screening and treatment, affected children develop typically optic atrophy, hypotonia, early onset seizures, developmental delay, and cutaneous manifestations. Some patients may have atypical presentations mimicking a demyelinating disorder of the central nervous system. We report on the first genetically confirmed Tunisian patient with biotinidase deficiency who presented initially with cutaneous manifestations misdiagnosed as dermatophytosis and subsequently with an opticospinal syndrome leading to the diagnosis of seronegative neuromyelitis optica spectrum disorder that was dramatically improved under biotin. We carry on a review of the literature of the previously reported pediatric cases with an opticospinal syndrome revealing biotinidase deficiency.